An efficient numerical method for earthquake cycles in heterogeneous media: Alternating subbasin and surface‐rupturing events on faults crossing a sedimentary basin. Issue 4 (22nd April 2014) - Erickson, Brittany A.; Dunham, Eric M.
<x xml:space="preserve">Abstract</x> We present an efficient numerical method for earthquake cycle simulations that employs a finite difference discretization of the off‐fault material to accommodate spatially variable elastic properties. The method is developed for the two‐dimensional antiplane shear problem of a vertical strike‐slip fault with rate‐and‐state friction. We compare earthquake cycles in a homogeneous half‐space with those in which the upper portion of the fault cuts through a sedimentary basin. In both cases, we assume velocity‐weakening behavior over the full seismogenic depth, even in the basin, to isolate the influence of elastic heterogeneity. In a homogeneous half‐space, events rupturing the full seismogenic depth occur periodically. Event sequences are more complex in basin models, with one or several subbasin events confined to the lower section of the fault followed by a much larger, surface‐rupturing event that breaks through the basin. This phenomenology emerges only for sufficiently compliant and deep basins. Predicted surface velocities are essentially identical before subbasin events and surface‐rupturing events, suggesting that geodetic observations would not be useful in predicting the rupture mode. The alternating sequence of subbasin and surface‐rupturing events would complicate interpretation of paleoseismic data. Our results also offer one potential explanation for the shallow slip deficit observed in many recent earthquakes, namely, that these events, which lack appreciable surface slip, are simply one style of rupture. Subsequent events on these faults might be larger, with slip extending all the way to the surface. The 1940 Mw 7.0 and 1979 Mw 6.5 Imperial Valley events might be considered as examples of these two rupture styles.